2009
DOI: 10.1016/j.otsr.2009.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Total knee arthroplasty with limitations of flexion

Abstract: level 4 retrospective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 16 publications
1
9
0
2
Order By: Relevance
“…Regarding range of motion, the improvement observed in our series is similar to that reported in other series in the literature [13][14][15][16][17]. These ranges are lower than those that can be expected in a population with osteoarthritis of the knee without significant associated stiffness.…”
Section: Discussionsupporting
confidence: 87%
“…Regarding range of motion, the improvement observed in our series is similar to that reported in other series in the literature [13][14][15][16][17]. These ranges are lower than those that can be expected in a population with osteoarthritis of the knee without significant associated stiffness.…”
Section: Discussionsupporting
confidence: 87%
“…The reported clinical results of TKA in patients with haemophilia have varied considerably with the prevalence of infection ranging from 0% to 17% and a rate of prosthetic survival of 90% after 5 years [1]. In the most recent literature, the rate of infection has ranged from 1.4% to 11.4%, with an average of 6.9% [2–5]. The 20‐year survival rate published by Goddard et al.…”
Section: Rate Of Infection In Total Knee Arthroplasties Performed Inmentioning
confidence: 99%
“…In the recent literature (2008–11), the average prevalence of infection was 6.9% [1–5] (Table 1). In the present study, it was 7%, which is much higher than the prevalence of 1–2% observed after total knee replacements in the non‐haemophilic population, and the one previously published by us of 2.8%.…”
Section: Rate Of Infection In Total Knee Arthroplasties Performed Inmentioning
confidence: 99%
“…Massin et al26) reported that improvements in flexion was not correlated with the postoperative function score. In the current study, the increase in maximal flexion angle was significantly greater by 10° in the study group, whereas there were no significant differences between the two groups in the knee score and function score.…”
Section: Discussionmentioning
confidence: 99%